GENESIS AND TRANSFORMATIONS OF THE EARLY SOCIETY OF THE BOOK IN THE GDL - CICĖNIENĖ, RIMA (Knygotyra, 2010)
Relinquishing the linguistic criterion in the cultural history of the GDL in order to better understand the cultural processes in the state (in its geographical and ethnoconfessional entirety) expanded the scope of research in manuscript book history. The subsequent inclusion in the research of books in the Latin, Ruthenian and Church Slavonic languages, written and read in the GDL, offered a possibility to focus on the social purpose of the book. The aim of this study was to establish the social context and transformations of the manuscript book phenomenon in the GDL from the 14th to the mid-16th century. For this purpose, we attempted to determine in which social strata the new cultural phenomenon – the book – took hold and to determine what forms of book functioning developed in these strata. The research combines several methods: source study, analysis, synthesis, the descriptive method, and the prosopography method (which is still new in book science). An analysis of 215 manuscript books (177 de visu and 38 descriptions in printed catalogues) as well as of archival documents and historiographical works enabled us to collect information about 163 persons in whose environment manuscript books functioned. Based on the present research, it may be suggested that early manifestations of book society in the GDL occurred already in the 14th century. In the middle of the 15th century, this society encompassed not only the rulers, princes and priests, but also the nobles, part of the townspeople and students. By the end of the century, the communication of the manuscript book acquired features of the full cycle. In the late 15th – early 16th century, the completely formed book society already encompassed diverse social strata. Meanwhile, the active spread of books, printed in Western Europe, interfered with the manuscript book existence.